Tinjauan Hukum Islam Terhadap Status Kepemilikan Emas Virtual Di Aplikasi Shopee - Dewi, Dewinta Sari; Yuniarti, Desi; Rosana, Mayang (Cross-border, 2024)
The aim of this research is to find out the mechanism for ownership of virtual gold through buying and selling on the Shopee application, and what the status of ownership of virtual gold on the Shopee application is from an Islamic legal perspective. The type of research seen from its type is included in qualitative field research, with a descriptive analysis approach. The results of the research conducted by researchers are first, regarding the mechanism of virtual gold ownership through buying and selling on the Shopee application in Islam, including imperfect ownership because it only consists of gold balance. Second, the status of virtual gold ownership in the Shopee application is considered invalid because it does not fulfill the muamalah agreement, namely the absence of handover of goods.